Symptoms of lower urinary tract in women who practice physical exercise regularly. - Barreto, Eliana; Filoni, Eduardo; Fitz, Fátima Faní (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: The practice of regular physical exercise provides benefits to health and quality of life. However, these are seen as promoters of dysfunctions of the pelvic floor muscles (PFMs). Objective: To evaluate the physical activity level and the presence of urinary symptoms in women who perform exercise regularly and check the relation between then. Method: Forty-seven women who practice regularly physical exercise were evaluated in two gyms in the State of São Paulo/Brazil. The participants were characterized in accordance with the age, number of pregnancies, parity, body mass index, waist circumference, duration of physical exercise, weekly frequency of exercise and time spent in physical exercise. The level of physical activity was assessed by the “International Physical Activity Questionnaire” (IPAQ) long form, and the presence of urinary symptoms and their severity were assessed by the International Consultation on Incontinence Questionnaire - Short Form (ICIQ-SF). Results: Approximately 51.9% of women were considered active (greater than 600 METs value) and 49.1% were considered highly active (more than 1500’s MET value). It was observed the presence UI in 72.3% of study participants. Approximately 52% of women showed a moderate UI according to the ICIQ-SF. Conclusion: Women were considered active or very active according to the recommendations of the IPAQ. It was observed a high prevalence of urinary symptoms in women on efforts in women who perform any physical activity regulary. The severity of the incontinence was classified as moderate according the ICIQ-SF. No significant relation it was observed between the severity of the UI and the level of physical activity.